It might raise you up or pull you down - The significance and possibility of improving reading and comprehension skills from junior high school - Gáborné, Demeter (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Acquiring information and knowledge is unobtainable without well-established reading and comprehension skills. The accuracy, automaticity and speed of these competencies affects the quality of an individual’s course of life to a huge extent: it might open a door to the world of letters, words and sentences, or might close the same door depriving the individual from the chance of social integration. A considerable amount of junior high school classes do not consider the conscious and universal improvement of reading and comprehension skills involving all subjects a task of their own. It is supposed that these competencies are already applied by students as tools in their everyday learning processes, based on their reading experience from the previous classes of primary school. However, this supposition proves to be without foundation in the case of more and more students. This study aims at providing help for educators working in junior or senior high school classes regarding the late improvement of reading and comprehension skills, which offers support not only in achieving success at school, but also in creating social opportunities.